KERUNTUHAN KEDAULATAN BANGSA: DAMPAK GLOBALISASI TERHADAP KEMANDIRIAN EKONOMI DAN POLITIK - Boy, Pradana (Jurnal Bestari, 2009)
Although Indonesia has been independent since 1945, this does mean that this country has economic autonomy. In term of economy, Indonesia highly depends on foreign powers and it is even exploited by those powers. Economic autonomy is a central issue in its relation with a nation's sovereignty. Apart from economy, another central pillar is political autonomy and independence. This article explores a strong desire to present indigenous and traditional economic and political values owned by Indonesia as a sovereign nation. Presenting these values is important in the midst of the intensification of ideological clash. This article highlights the urgency of Indonesia being economically and politically autonomous using globalization as main setting.